2002
DOI: 10.1002/cncr.10936
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin 1 and neuropilin 2 co‐expression is significantly correlated with increased vascularity and poor prognosis in nonsmall cell lung carcinoma

Abstract: BACKGROUND Cell‐retained isoforms of vascular endothelial growth factor A (VEGF‐A) have been reported to play an essential role in tumor progression through stromal neovascularization in malignant solid tumors. While more than 95% of nonsmall cell lung carcinoma (NSCLC) expresses cell‐retained VEGF‐A isoform, the clinicopathologic implications of neuropilin (NRP), considered the specific receptor for limited types of VEGF‐A isoform, are not well understood. METHODS The authors examined NRP1 and NRP2 mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 29 publications
5
145
0
Order By: Relevance
“…Accumulating evidence suggests that neuropilin-1 is overexpressed in several cancers and its high expression is correlated with poor prognosis (Ding et al, 2000;Kawakami et al, 2002;Roche et al, 2002;Vanveldhuizen et al, 2003;Broholm and Laursen, 2004;Fukahi et al, 2004;Li et al, 2004;Osada et al, 2004;Parikh et Figure 8 Semaphorin3A (Sema3A) expression in human glioblastoma multiformes (GBMs). (a) Immunohistochemical analysis of Sema3A in human GBM tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence suggests that neuropilin-1 is overexpressed in several cancers and its high expression is correlated with poor prognosis (Ding et al, 2000;Kawakami et al, 2002;Roche et al, 2002;Vanveldhuizen et al, 2003;Broholm and Laursen, 2004;Fukahi et al, 2004;Li et al, 2004;Osada et al, 2004;Parikh et Figure 8 Semaphorin3A (Sema3A) expression in human glioblastoma multiformes (GBMs). (a) Immunohistochemical analysis of Sema3A in human GBM tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of neuropilin-1 has been observed previously in several cancers, including GBMs, and its high expression is correlated with poor prognosis (Kawakami et al, 2002;Osada et al, 2004;Kreuter et al, 2006 Figure 1 Functional proteomic screen identifies neuropilin-1 as a mediator of cancer cell invasion. (a) Overview of the proteomic screen.…”
Section: Functional Proteomic Screen Identifies Neuropilin-1 As a Medmentioning
confidence: 92%
“…[8][9][10] The cells (passages [20][21][22][23][24][25][26][27][28][29][30] were grown at 371C in a humidified 5% CO 2 atmosphere, and split at a 1:10 ratio, once a week. After growth to a subconfluent state, cells were washed once, made quiescent by incubation in serum-and supplementfree medium for 48 h, and then used for experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…29 Co-expression of NRP1 and NRP2 also increased in the progression from dysplasia to microinvasive lung carcinoma, and correlated significantly with tumor progression and poor prognosis in patients with nonsmall-cell lung carcinoma. 30 Although most studies have indicated a pro-tumorigenic role of NRPs, some reports suggest that NRP1 has a more complex role in some tumor types. NRP1 overexpression in Panc-1 cells was found to reduce tumor volume and incidence, 31 and there is also evidence pointing to potentially differential or antagonistic roles of NRP1 and NRP2 in tumor cell regulation.…”
Section: Differential Neuropilin Expression In Fsgsmentioning
confidence: 99%
“…However, BC cells/tissues as well as other malignancies express various amounts of other VEGF receptors, neuropilins‐1/2 19, 20, 21, 22. One neuropilin, NRP1, is a transmembrane protein that consists of a large extracellular domain, one transmembrane domain, and a relatively short cytoplasmic tail.…”
Section: Introductionmentioning
confidence: 99%